VISproPT: A high-precision instrument for 3D shape analysis of parabolic trough panels [version 1; peer review: 2 approved, 1 approved with reservations] - Marco Montecchi; Giuseppe Cara; Arcangelo Benedetti (Open Research Europe, 2023)
In Concentrating Solar Power plants, reflective panels are used to redirect solar radiation towards a receiver. Because the panel shape drives the radiation distribution around the focus where the receiver is placed, the 3D measurement is fundamental to assess the panel shape quality. The VISproPT instrument is the advanced version of the prototype VISprofile; these instruments are designed for indoor measuring of the 3D shape of parabolic-trough reflective panels. The VIS proPT hardware has been manufactured by MARPOSS Italia Spa and funded by EU project ’Solar Facilities for the European Research Area - Third Phase’ (SFERA-III), while the image processing software as well as the calibration procedure, based on the measurement of a perfectly flat surface as that of a calm body of water, have been developed by Italian National Agency for New Technologies, Energy and Sustainable Economic Development (ENEA). The instrument precision is better than 0.1 mrad and 0.3 mm (root mean square value over an area 1.2 × 0.8 m2), for slope and height of the surface respectively. Technical details of experimental set up and calibration-procedure are here reported. The instrument effectiveness is shown by reporting the results obtained on a set of 10 specimen (5 inner + 5 outer) adopted to run the SFERA-III WP10 Task3 round-robin on 3D shape measurements among the different instruments used by the Fraunhofer Institute for Solar Energy Systems ISE (F-ISE), Deutsches Zentrum Fuer Luft - und Raumfahrt EV (DLR), the National Renewable Energy Laboratory (NREL) and Sandia National Laboratories (SANDIA).